2005
DOI: 10.1038/sj.onc.1208910
|View full text |Cite
|
Sign up to set email alerts
|

Frequent epigenetic inactivation of Wnt inhibitory factor-1 in human gastrointestinal cancers

Abstract: Aberrant activation and upregulation of the Wnt pathway is a key feature of many cancers. Wnt antagonists have recently attracted wide attention. Wnt inhibitory factor-1 (WIF-1) is a secreted antagonist that can bind to Wnt proteins directly and inhibit Wnt signaling pathway. It has been reported that WIF-1 expression is down regulated in several solid tumors and that WIF-1 is silenced by promoter hypermethylation in lung and colorectal cancer. By using RT-PCR, bisulfite sequence analysis, and methylation-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
142
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 20 publications
(35 reference statements)
8
142
3
Order By: Relevance
“…WIF1 is a secreted Wnt antagonist that is often downregulated because of genomic rearrangement, genomic loss or promoter hypermethylation in several human tumors, including colon, lung, breast, prostate, bladder, kidney and salivary gland (Wissmann et al, 2003;Byun et al, 2005;Taniguchi et al, 2005;Ai et al, 2006;Urakami et al, 2006;Queimado et al, 2008;Kawakami et al, 2009). Our study demonstrates that WIF1 downregulation is an early and widespread event in human cervical oncogenesis, which occurs frequently due to promoter hypermethylation.…”
Section: Discussionmentioning
confidence: 64%
“…WIF1 is a secreted Wnt antagonist that is often downregulated because of genomic rearrangement, genomic loss or promoter hypermethylation in several human tumors, including colon, lung, breast, prostate, bladder, kidney and salivary gland (Wissmann et al, 2003;Byun et al, 2005;Taniguchi et al, 2005;Ai et al, 2006;Urakami et al, 2006;Queimado et al, 2008;Kawakami et al, 2009). Our study demonstrates that WIF1 downregulation is an early and widespread event in human cervical oncogenesis, which occurs frequently due to promoter hypermethylation.…”
Section: Discussionmentioning
confidence: 64%
“…35,36 In a recent study, WIF1 was found to be silenced epigenetically in a limited number of Japanese ESCC cell lines and primary tumors. 15 We have systematically analyzed a larger series of ESCC cell lines and a much larger number of primary tumors from Hong Kong Chinese as well as paired normal esophageal tissues, NEE tissues and normal cell lines. The results from these two ethnic groups were similar.…”
Section: Discussionmentioning
confidence: 99%
“…WIF1 was found to be downregulated by methylation in various human malignancies including carcinoma of lungs, mesothelioma, colorectal, various urological and gastrointestinal malignancies. [14][15][16] We also reported that WIF1 is frequently inactivated by methylation in breast cancer. 17 Compared with the low incidence in other parts of the world, nasopharyngeal carcinoma (NPC) and esophageal squamous cell carcinoma (ESCC) are both prevalent malignancies in Southern Asia including Southern China such as Hong Kong, with annual incidence reaching B30 and B100/ 100 000, respectively.…”
mentioning
confidence: 99%
“…To perform semiquantitative RT-PCR, the ranges of linear amplification for the CASR gene and for the GAPDH gene were studied by using standard curves. 26 Thus, the optimal number of PCR cycles was determined. After PCR, the PCR products were electrophoresed in 2% agarose gels.…”
Section: Semiquantitative Rt-pcr and Real-time Rt-pcrmentioning
confidence: 99%